Salt Stress Induces Paramylon Accumulation and Fine-Tuning of the Macro-Organization of Thylakoid Membranes in Euglena gracilis Cells - Kanna, Sai Divya; Domonkos, Ildikó; Kóbori, Tímea Ottília; Dergez, Ágnes; Böde, Kinga; Nagyapáti, Sarolta; Zsiros, Ottó; Ünnep, Renáta; Nagy, Gergely; Garab, Gyözö; Szilák, László; Solymosi, Katalin; et al. (Frontiers in Plant Science, 2021)
The effect of salt stress condition on the growth, morphology, photosynthetic performance and paramylon content were examined in the mixotrophic, unicellular, flagellate Euglena gracilis. We found that salt stress negatively influenced the cell growth, accompanied by a decrease of the chlorophyll content. Circular dichroism spectroscopy revealed changes in the macro-organization of pigment-protein complexes due to salt treatment, while small-angle neutron scattering (SANS) investigations suggested reduction in the thylakoid stacking, an effect confirmed by transmission electron microscopy. At the same time, analysis of the thylakoid membrane complexes using native-PAGE revealed no significant change in the composition of supercomplexes of the photosynthetic apparatus. Salt stress did not substantially affect the photosynthetic activity, as reflected by the facts that chlorophyll fluorescence yield, electron transport rate and energy transfer between the photosystems did not change considerably in the salt-grown cells. We have observed notable increases in the carotenoid-to-chlorophyll ratio and the accumulation of paramylon in the salt-treated cells. We propose that accumulation of storage polysaccharides and changes in the pigment composition and thylakoid membrane organization help the adaptation of Euglena gracilis cells to salt stress and contribute to the maintenance of cellular processes under stress conditions.